Electron microscopic visualization of capsular material of Pasteurella multocida types A and D labeled with polycationic ferritin. - Jacques, M (1987)
The presence of capsular material on cells of Pasteurella multocida types A and D was determined by transmission electron microscopy after polycationic ferritin labeling. The capsule of agar-grown isolates of P. multocida type A was thick (70 to 90 nm) and regular, whereas that of type D isolates was thinner (20 to 30 nm) and irregular. Such layers were seen on cells from 4- to 6-h broth cultures, but cells from older cultures (12 to 18 h) had very little cell-associated capsular material. Our data indicate that the capsular material of P. multocida types A and D is morphologically different and that capsule production in broth culture is maximal during early log phase.